(untitled) (Medical Forum Monthly, 2024)
Objective: To study the clinical features, role of mobile plasmapharesis unit and outcome in patients with acute inflammatory demyelinating polyradiculoneuropathy (AIDP). Study Design: Retrospective Cross Sectional Study Place and Duration of Study: This study was conducted at Neurology Department, KEMU, Lahore from July 2008 till June 2012. Materials and Methods: Patients from various hospitals (both public and private) fulfilling the Ashbury and Cornblath’s Clinical Diagnostic Criteria for GBS and requiring plasmapharesis were included in the study. For this purpose a special proforma was designed to be filled by the primary physician at the time of request for mobile plasmapharesis service. This service was provided by a donor organization namely Pakistan Myasthenia Gravis Welfare Organization (PMWO) based at a public hospital in Lahore. Plasmapharesis was started according to the guidelines, as soon as possible after admission, if patient had history of progressive weakness. The protocol of this treatment was to exchange 200 to 250 ml of plasma per kilogram of body weight in five sessions within 7 to 10 days. The replacement fluids most often consist of 0.9% normal saline, haemaccel and/or albumin. Recovery was assessed by modified Hughes Guillain-Barré syndrome disability scale. Results: A total of 152 patients were included in the study with 94 (61.8%) males and 58 (38.2%) females and M: F ratio of 1.62:1. The mean age was 32.66 (SD 15.89) with range from 7-80 years. One hundred and nine (72%) cases presented between 11-40 years of age. All patients were treated with five sessions of plasmapharesis. Drop out rate for plasmapharesis was 1.5% implying its good tolerability Out of the total of 152 cases, 149 (98%) cases presented with progressive areflexic weakness and 3 (2%) patients with bilateral external Ophthalmoplegia, areflexia and ataxia (Miller-Fisher variant). Sensory symptoms were present in 31(20.4%), bulbar weakness in 29(19.1%), and bilateral facial weakness in 25(16.4%) cases. Severe respiratory distress requiring ventilatory support occurred in 36(23.7%) cases. Pearson’s correlation revealed that gender and age were not risk factors for the development of ventilatory failure (p=0.354; 0.803), bilateral facial weakness (p = 0.121; 0.473) or bulbar weakness (p= 0.383; 0.745) respectively. Overall mortality was 5% and all these cases developed severe respiratory distress and needed ventilatory support. Complete recovery occurred in 90% cases and 5% had residual deficit (Hughes disability scale severity 1 & 2) at mean follow up of six months. Conclusions: Our study showed that GBS is statistically more frequent in males than females in our local population with maximum frequency between 11-40 years of age range. However, the two factors i.e. gender and age has no significant association with the development of ventilatory failure, bilateral facial weakness and bulbar weakness. Areflexic motor weakness was the commonest presenting feature. Plasmapharesis remained very effective therapeutic option which is cheaper and affordable in our poor socio-economic setting. Mobile unit service provided an excellent opportunity to treat most of these patients at their native hospitals. We recommend that government and donor organizations should develop more mobile plasmapharesis services in all major cities which can cover nearby district and tehsil hospitals.